Investigating Mathematics Teachers’ Understanding and Practices of Learner-centered Teaching in Junior Secondary Schools within Katima Circuit in the Zambezi Region of Namibia - Mwazi, Richard Salufu; Garegae, Kgomotso Gertrude; Katukula, Kelvin Mubiana; Kambeyo, Linus (Innovare Journal of Education, 2023)
This study investigated mathematics teachers’ understanding and practices of learner-centered teaching (LCT) in junior secondary schools within Katima Circuit in the Zambezi Region of Namibia. A qualitative study method was used and purposeful sampling procedures were used to select participants. Research instruments included open-ended interviews and recordings from twenty mathematics teachers in selected junior secondary schools in the Zambezi Region. Results of the study indicate that teachers understand the concepts of LCT and have adequate training and knowledge on the benefits and teaching approach in LCT due to the inclusion of the LCT methods in teacher education and other training workshops. However, the study also found that most mathematics teachers use only cooperative learning during teaching and learning mathematics. The study also identified significant challenges teachers face in implementing LCT, including overcrowded classrooms, lack of resources, and learners’ lack of motivation. Considering the above findings, the study recommends that the government and stakeholders support teachers with resources and further staff development opportunities.